2021
DOI: 10.48550/arxiv.2107.11307
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Radio signals from early direct collapse black holes

B. Yue,
A. Ferrara

Abstract: We explore the possibility to detect the continuum radio signal from direct collapse black holes (DCBHs) by upcoming radio telescopes such as the SKA and ngVLA, assuming that after formation they can launch and sustain powerful jets at the accretion stage. We assume that the high-𝑧 DCBHs have similar jet properties as the observed radio-loud AGNs, then use a jet model to predict their radio flux detectability. If the jet power 𝑃 jet 10 42βˆ’43 erg s βˆ’1 , it can be detectable by SKA/ngVLA, depending on the jet … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 89 publications
(112 reference statements)
0
1
0
Order By: Relevance
“…Nascent DCBHs would be free of competing sources of radio emission in their host halos that are present in CR7, such as young supernova remnants (SNRs; Meiksin & Whalen 2013) and H II regions due to star formation (Condon 1992), because they form in halos before other stars. Yue & Ferrara (2021) recently estimated DCBH radio fluxes under the assumption that they drive strong jets and found that they should be detectable by the SKA and ngVLA at z ∼ 10, depending on the inclination angle of the jet. However, steady jets have only been observed in active galactic nuclei with luminosities L 0.01 L Edd , where L Edd is the Eddington limit, and intermittent jets have been seen in quasars at L ∼ L Edd (Merloni & Heinz 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Nascent DCBHs would be free of competing sources of radio emission in their host halos that are present in CR7, such as young supernova remnants (SNRs; Meiksin & Whalen 2013) and H II regions due to star formation (Condon 1992), because they form in halos before other stars. Yue & Ferrara (2021) recently estimated DCBH radio fluxes under the assumption that they drive strong jets and found that they should be detectable by the SKA and ngVLA at z ∼ 10, depending on the inclination angle of the jet. However, steady jets have only been observed in active galactic nuclei with luminosities L 0.01 L Edd , where L Edd is the Eddington limit, and intermittent jets have been seen in quasars at L ∼ L Edd (Merloni & Heinz 2008).…”
Section: Introductionmentioning
confidence: 99%